Groundwater exploration using Vertical Electrical Sounding (VES) Method at Toro Jaya, Langgam, Riau - Suryadi, Adi; Putra, Dewandra Bagus Eka; Kausarian, Husnul; Prayitno, Budi; Fahlepi, Reza (UIR PRESS, 2018)
Vertical Electrical Sounding (VES) method is one of many methods in geophysics that was conducted in this research at Toro Jaya, Langgam, Riau. The aim of this research is to investigate and locate the depth of groundwater layer (aquifer). Data acquisition of VES was carried out using GEOCIST with Schlumburger configuration of electrode. There are four VES point in this research with various length of cable ranging from 135 m up to 200 m. From four VES point shown two different of resistivity value range. Very low resistivity value with range 0,34 – 0,9 Ωm interpreted as aquifer layer. The aquifer layer of research area divided into two types which are unconfined aquifer and confined aquifer. Meanwhile, another resistivity value ranging from 1,69 – 7  Ωm was interpreted as clay layers.